Pericardium 6 (PC6) Acupressure in Reducing the Frequency of Emesis Gravidarum in First Trimester Pregnant Women in the Work Area of Community Health Center X - Hastuti Marlina; Sherly Vermita Warlenda (Jurnal Multidisiplin Madani, 2022)
This study aimed to determine the effectiveness of one of the non-pharmacological therapies for emesis gravidarum, namely PC6 acupressure massage, on the frequency of emesis gravidarum at Community Health Center X. The study design was quasi-experimental with two groups of pre-test and post-test designs. The sample consisted of 30 people, 15 for the experimental group and 15 for the control group. The sampling technique is purposive sampling with specific inclusion criteria. The results of the study based on the Wilcoxon test, it was known that there was a decrease in emesis gravidarum in first trimester pregnant women before and after acupressure massage at the PC6 point for the experimental and control groups. While the results of the Mann-Whitney test obtained a p-value of 0.324 > 0.05, meaning that between the experimental group and the control group, there was no difference in the decrease in the frequency of emesis gravidarum.